"From a Family Home to Hell": Experiences and Consequences of Intimate Partner Violence Among Married Jordanian Women. (2nd January 2019) - Shoqirat, Noordeen; Almajali, Ayah; Alsaraireh, Arwa
Abstract: This study aimed to understand the experience of intimate partner violence (IPV) and related consequences among married Jordanian women. A qualitative exploratory design using semi-structured interviews ( n  = 10) was employed. Analysis of the qualitative data revealed two main themes. The first theme focused on the transition: "From a family home to Hell". The second theme was described as the path from wellness to illness, including an analysis of the various consequences of IPV. A continuous educational program for the victims themselves and healthcare professionals along with a serious partnership with legal and political institutions in Jordan is urgently needed.